Anti-Methodism in Eighteenth-Century England: The Pendle Forest Riots of 1748 - Snape, Michael (The journal of ecclesiastical history, 1998)
Notice is hereby given, that if any man be mindful to enlist in his Majesty's service, under the command of the Rev. Mr. George White, Commander-in-Chief, and John Bannister, Lieut.-General of his Majesty's forces for the defence of the Church of England, and the support of the manufactory in and about Colne, both which are now in danger, let him repair to the drum-head at the Cross, where each man shall receive a pint of ale in advance, and all other proper encouragements.This notice, which was published at the height of the agitation which beset the forest of Pendle in the summer of 1748, conjures images beloved of the Methodist hagiographer. Assuming quasi-military titles, squire and parson rally a drink-sodden mob to do battle against the preachers of the Gospel, and all in the name of religion and commerce. Historians, however, are required to take a more dispassionate view of the motives and actions of those who, through violence or polemic, attempted to arrest the growth of the Evangelical Revival, a movement which was to prove one of the most influential religious and cultural movements in the history of the British Isles. John Walsh's pioneering essay on ‘Methodism and the mob’ was one of the first serious attempts to treat anti-Methodist agitation sympathetically, and to place it in the much broader context of the norms of popular protest in the eighteenth century. However, detailed academic studies of anti-Methodist protests remain scarce, and the strong correlation between these and other examples of popular hostility towards other deviant religious groups, such as Catholics, Nonconformists and Jews, remains understated.